OPTIMIZATION OF ROOFTOP SOLAR POWER PLANT DESIGN AT THE BAPENDA BILDING, WEST JAVA - Alfiandito, Denaro; Faridah, Linda; Usrah, Ifkar (Jurnal Kajian Teknik Elektro, 2025)
Dependence on fossil fuels as the primary source of electricity has led to various environmental emissions and long-term energy security concerns, especially as electricity demand continues to rise. Transitioning to renewable energy sources is a crucial step in addressing these issues. One strategic solution is the implementation of rooftop Solar Power Plants (PLTS), in line with the Indonesian government's target to increase the share of renewable energy to at least 23% by 2025 and 31% by 2050. The solar irradiation potential in the Buahbatu area of Bandung City reaches 5.19 kWh/m²/day, offering significant potential for solar energy utilization. This study focuses on the design of a rooftop PLTS for the BAPENDA building in West Java using PVsyst software to determine the system configuration, component selection, and energy production simulation. The available rooftop area of 228 m² is utilized for the installation of the PLTS. Simulation results indicate that the system can accommodate 110 photovoltaic (PV) modules with a capacity of 380 Wp, covering an area of 218 m². The system is supported by 10 inverters, each with a capacity of 4 kW. The total annual energy production from the PLTS reaches 67,198 kWh, compared to the building’s annual energy consumption of 353,011 kWh. Additionally, approximately 23 kWh of surplus energy is exported back to the PLN grid. The findings demonstrate that the implementation of a rooftop PLTS can significantly reduce dependence on conventional energy sources, contribute to carbon emission reductions, and support national renewable energy targets